2021
DOI: 10.3390/en14248462
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Synthetic Component on the Emission of Volatile Organic Compounds during the Combustion Process in a Miniature Turbine Engine

Abstract: This paper refers to the study of biofuel as an alternative power source for turbine aviation engines. Blends of Jet A-1 fuel and synthesized hydrocarbons from Hydrotreated Esters and Fatty Acids (HEFA) technology at different proportions, such as 25%, 50% and 75%, were used for tests. All the test results were compared with the neat Jet A-1 fuel. A miniature GTM series turbojet engine was used in the test rig studies. During the tests conducted at a specific rotational speed, selected engine operating paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Analyses of this type require researchers to optimize sample collection and determine an appropriate analytical method. A literature review showed that scientists use a number of available methods of collecting research material and chromatographic methods, i.e., GC-MS [6][7][8][9][10][11][12][13][14], LC-MS [15], TD-GC-MS [16] with sampling into sorbent tubes [14], feeding whole air or raw exhaust gases into Tedlar bags [9,[17][18][19][20][21][22][23], microextraction into the solid phase [24], or the flame ionization method [25][26][27]. In the work of other research centers [22,23], volatile organic compounds were collected from two-wheeled vehicles into a set of Tedlar bags.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of this type require researchers to optimize sample collection and determine an appropriate analytical method. A literature review showed that scientists use a number of available methods of collecting research material and chromatographic methods, i.e., GC-MS [6][7][8][9][10][11][12][13][14], LC-MS [15], TD-GC-MS [16] with sampling into sorbent tubes [14], feeding whole air or raw exhaust gases into Tedlar bags [9,[17][18][19][20][21][22][23], microextraction into the solid phase [24], or the flame ionization method [25][26][27]. In the work of other research centers [22,23], volatile organic compounds were collected from two-wheeled vehicles into a set of Tedlar bags.…”
Section: Introductionmentioning
confidence: 99%